PERANCANGAN BASIS DATA PENDAPATAN CARGO DAN PENCATATAN DATA PELANGGAN MENGGUNAKAN VISUAL BASIC 6.0 PADA PT INTAN LUBUK PERTAMA - Ginanti, Maulidya Sahira; Evayani, Evayani (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The purpose of this reaseach is to determine how the income accounting information systems and customer data records that are running at PT Intan Lubuk Pertama. The company is still using manual systems to perform each transaction. This resulted in the company slow in presenting relevant information, so can not work effectively and optimally in serving the required reports. According to these problems, the authors are interested in doing research with the title